A Review of the Microstructural Location of Impurities in Polar Ice and Their Impacts on Deformation - Stoll, Nicolas; Eichler, Jan; Hörhold, Maria; Shigeyama, Wataru; Weikusat, Ilka (Frontiers in Earth Science, 2021)
Insoluble and soluble impurities, enclosed in polar ice sheets, have a major impact on the deformation behaviour of the ice. Macro- and Micro-scale deformation observed in ice sheets and ice cores has been retraced to chemical loads in the ice, even though the absolute concentration is negligible. And therefore the exact location of the impurities matters: Allocating impurities to specific locations inside the ice microstructure inherently determines the physical explanation of the observed interaction between chemical load and the deformational behaviour. Both, soluble and non-soluble impurities were located in grain boundaries, triple junctions or in the grain interior, using different methods, samples and theoretical approaches. While each of the observations is adding to the growing understanding of the effect of impurities in polar ice, the growing number of ambiguous results calls for a dedicated and holistic approach in assessing the findings. Thus, we here aim to give a state of the art overview of the development in microstructural impurity research over the last 20 years. We evaluate the used methods, discuss proposed deformation mechanisms and identify two main reasons for the observed ambiguity: 1) limitations and biases of measurement techniques and 2) the physical state of the analysed impurity. To overcome these obstacles we suggest possible approaches, such as the continuous analysis of impurities in deep ice cores with complementary methods, the implementation of these analyses into established in-situ ice core processing routines, a more holistic analysis of the microstructural location of impurities, and an enhanced knowledge-transfer via an open access data base.